Influence of absorbed water on the dielectric properties and glass-transition temperature of silica-filled epoxy nanocomposites - Zou, C.; Fu, M.; Fothergill, J.C.; Rowe, S.W. (2006 IEEE Conference on Electrical Insulation and Dielectric Phenomena, 2006)
Work on dielectric spectroscopy of epoxy resin filled with nano-SiO 2 at different relative humidities and temperatures is reported. Above the glass-transition temperature (T g ), dc-like imperfect charge transport (QDC or LFD) dominates the low frequency dielectric spectrum. Another mid-frequency relaxation process was found in the non-dried composites. Water also induces glass-transition temperature decreases, which can be measured both by dielectric spectroscopy and DSC. Both theory and experiment demonstrated that a higher water content could exist in nanocomposites than unfilled epoxy suggesting a bigger free volume when nanostructured. In our system, the hydrophilic surface of silica is likely to cause water to surround and lead to delamination of the epoxy from SiO 2 . This is a potential mechanical and dielectric weakness in the nanocomposites, which may lead to an ageing phenomenon. Hydrophobic surface group may reduce the water adsorption in nanocomposites.